The Indonesia’s Public’s Level of Knowledge Regarding Messages About the Labuan Bajo Super Priority Tourism Destination - Angela Tiffany; Felicia Goenawan (Scriptura, 2026)
Tourism destination messages have an important role in introducing the identity, potential and values ​​of a tourist location to the public. In the process, the message can be conveyed through various media, and it is necessary to see the level of public knowledge of the message. Labuan Bajo as one of the Super Priority Tourism Destinations (DPSP) designated by the government has a tourism message that focuses on marine tourism, conservation and culture. This research was conducted to determine the level of public knowledge of these three messages using the level of knowledge theory which is divided into 3 types, namely, Declarative knowledge, Procedural Knowledge, and Self-Regulatory Knowledge. This research uses a descriptive quantitative approach and an online survey method which was distributed to 400 respondents (Indonesian people) who had never visited Labuan Bajo. The results show that Indonesian people have the highest level of knowledge regarding the Labuan Bajo tourism destination message, especially in Declarative Knowledge, and lower in the Procedural Knowledge indicator. Thus, it can be concluded that the Indonesian people who participated in this research have higher knowledge of information than procedural knowledge. These findings imply that tourism communication should not only emphasize information but also provide more practical and experience-oriented messages that help potential visitors understand how to engage with the destination. Strengthening procedural knowledge through digital campaigns, storytelling, and interactive tourism content may enhance destination awareness and encourage future visitation.